Prenatal Nondiscrimination Laws: Disability, Social Conservatism, and the Political Economy of Genetic Screening - Denbow, Jennifer M. (Disability Studies Quarterly, 2020)
This article analyzes recent state laws and legislative debates in the United States concerning the prohibition of abortions performed because of a diagnosis of fetal disability. The article brings together critical theories to analyze the legislative records—including floor debates and committee hearings—in the four states that enacted disability PRENDAs before 2019. This analysis shows how social conservatives use disability PRENDAs to present themselves as the protector of the oppressed, while advancing their views about family and gender. Furthermore, I argue that PRENDAs place the burden for structural economic and political concerns on the shoulders of individuals, especially pregnant persons, while largely ignoring the medical-industrial complex as well as the government's own poor funding of social services for people with disabilities. Critical attention thus needs to be paid to how factors such as the ascendancy of genetics, the privatization of medicine, and the state's facilitation of capital accumulation for biotechnology corporations help constitute the ideal self-regulating risk-averse pregnant neoliberal subject. To bring attention to these factors, the article examines the political economy of non-invasive prenatal tests (NIPTs).